2020
DOI: 10.5114/biolsport.2020.96943
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of small-sided games combined with running drills on internal and external loads in young soccer players.

Abstract: The purpose of this study was to compare the effects of regular small-sided games (SSGreg) and SSGs combined with running drills (SSGcom) on players’ internal and external loads. Eighteen young male soccer players (average age: 18.2 ± 0.5 years) participated in 3 vs. 3 and 4 vs. 4 games, under both SSGreg and SSGcom conditions. SSGreg bouts were played for 4 minutes without additional running drills, while SSGcom bouts consisted of 3 min 30 s SSG and 15 s running before and after the bout, making the duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 34 publications
1
28
1
Order By: Relevance
“…Comparing the external load with previous studies, Köklü and colleagues (2020) [16] obtained results for the total distance between 1900 and 2300 m. These results are higher than those of our study, that is, 1000 and 1300 m. In our study, the activity time was 45 min, while for Köklü and colleagues (2020) [16], the activity duration is 90 min. Furthermore, the size of the SSGs format of Köklü and colleagues (2020) [16] was larger (20 × 30 m), causing an increase in total distance. With SSGs formats like the one in our research, Castellano and colleagues (2016) [30] obtained a total distance lower than in our study (530 m).…”
Section: External Loadcontrasting
confidence: 79%
See 3 more Smart Citations
“…Comparing the external load with previous studies, Köklü and colleagues (2020) [16] obtained results for the total distance between 1900 and 2300 m. These results are higher than those of our study, that is, 1000 and 1300 m. In our study, the activity time was 45 min, while for Köklü and colleagues (2020) [16], the activity duration is 90 min. Furthermore, the size of the SSGs format of Köklü and colleagues (2020) [16] was larger (20 × 30 m), causing an increase in total distance. With SSGs formats like the one in our research, Castellano and colleagues (2016) [30] obtained a total distance lower than in our study (530 m).…”
Section: External Loadcontrasting
confidence: 79%
“…This difference could be because the group of SSGs performed a greater number of movements and accelerations, producing an increase in heart rate compared with the group of strength training combined with SSGs. Compared with previous research in the variables of HR and a%HR, the work of [ 16 ] obtained a HR between 173 and 176 and a %HR max of around 88% in SSGs in 3 × 3 and 4 × 4 formats in young soccer players. Owing to the smaller size of the practice space (our study’s SSGs were approximately 20 × 10 m in size), our study obtained better results in both physical training programs, with 191 bpm and 96% HR max, and in SSGs, with 189 bpm and 92%, respectively.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In line with this, our results demonstrated higher RPE values on Tuesday for ES-SSG in comparison to G-SSG, but no differences were found for the other training sessions. A previous study showed that replacing 30 s within the 4-min bouts of SSG (both 3- and 4-a-side) with 2 x 15 s of running drills was effective in increasing internal (blood lactate and RPE) and external loads (moderate and high-intensity running) in young soccer players [ 49 ]. Bearing these findings in mind, it would be advisable to use a tapering strategy during the last 2 weeks of the intervention in amateur and professional soccer players, by reducing exponentially the training volume by 41–60% while maintaining both the intensity and the frequency of sessions, in order to maximize performance gains [ 50 52 ].…”
Section: Discussionmentioning
confidence: 99%